Analisa Perencanaan Kapasitas Produksi Fiber Polyester Menggunakan Metode Double Moving Average dan Regresi Linear - Hamidah, Putri Sekar; Suseno, Agustian; Nugraha, Billy (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Increasing demand and changing consumer desires over time have triggered the company PT. XYZ to try to fulfill the desires and follow product developments among consumers. This research is research that aims to analyze the production capacity of polyester fiber with several forecasting methods as consideration between the two, namely Double Moving Average and Linear Regression. This research is located at PT. XYZ, in this research only examined the production of polyester fibers. The Double Moving Average method shows that the error rate in the form of Mean Squared Error produces 24,891 polyester fiber items, while the Linear Regression method shows that the error rate in the form of Mean Squared Error produces 594 polyester fiber items. So a comparison between the two forecasting methods shows that the Linear Regression method has the smallest error rate and is the best method for producing polyester fiber for the following months.